(untitled) (Comparative & International Education Series, 2022)
This qualitative study aims to understand whether and how Central Asian female students’ identities change because of their studies in American higher education and cross-cultural encounters. Using an interpretive approach, I interviewed six female students from five countries of Central Asia: Kazakhstan, Kyrgyzstan, Turkmenistan, Uzbekistan, and Tajikistan. The study is based on the Reconceptualized Model of Multiple Dimensions of Identity (Abes, Jones, & McEwen, 2007), the Affective, Behavioral, and Cognitive Model of Culture Shock (Ward, Bochner, & Furnham, 2001), and the transnational feminist perspective (Grewal & Kaplan, 1994). The findings of the study demonstrate the ambivalent nature of participants’ views on their certain identity dimensions, emphasize how education accelerates the transformation process, and explore the female students’ feelings of disturbance and in-betweenness. The study concludes by suggesting that universities should not view students’ identity change as a pathology, but to understand the sense of in-betweenness and accept this complexity that is still in process.